The Victim-Offender Overlap in Intimate Partner Violence: Considering the Role of Self-control. Issue 6 (3rd June 2021) - Spivey, Emily; Nodeland, Brooke
ABSTRACT: Although a growing body of literature in the field of criminal justice documents the relationship between victimization and offending, only recently has this knowledge been applied to the study of intimate partner violence (IPV). Utilizing data obtained from the National Longitudinal Study of Adolescent to Adult Health (Add Health), we examine whether low self-control predicts IPV victimization, IPV offending, or both IPV victimization and offending. Specifically, the study extends prior literature by (1) investigating the influence of self-control on the victim-offender overlap in IPV, (2) using longitudinal data, and (3) utilizing a sample of U.S. adults ages 24 to 33. While low self-control was found to significantly predict IPV offending and the overlap in IPV victimization and offending, low self-control failed to significantly predict IPV victimization.